An ancient F-type subdwarf from the halo crossing the Galactic plane - Scholz, R. -D.; Heber, Ulrich; Heuser, Christian; Ziegerer, Eva; Geier, Stephan; Niederhofer, F (Astronomy & Astrophysics, 2015)
Aims. We selected the bluest object, WISE J0725-2351, from Luhman's new high proper motion (HPM) survey based on observations with the Wide-field Infrared Survey Explorer (WISE) for spectroscopic follow-up observations. Our aim was to unravel the nature of this relatively bright (V similar to 12, J similar to 11) HPM star (mu = 267 mas/yr).Methods. We obtained low-and medium-resolution spectra with the European Southern Observatory (ESO) New Technology Telescope (NTT)/EFOSC2 and Very Large Telescope (VLT)/X-Shooter instruments, investigated the radial velocity and performed a quantitative spectral analysis that allowed us to determine physical parameters. The fit of the spectral energy distribution based on the available photometry to low-metallicity model spectra and the similarity of our target to a metal-poor benchmark star (HD 84937) allowed us to estimate the distance and space velocity.Results. As in the case of HD 84937, we classified WISE J0725-2351 as sdF5: or a metal-poor turnoff star with [Fe/H] = -2.0 +/- 0.2, T-eff = 6250 +/- 100 K, log g = 4.0 +/- 0.2, and a possible age of about 12 Gyr. At an estimated distance of more than 400 pc, its proper motion translates to a tangential velocity of more than 500 km s(-1). Together with its constant (on timescales of hours, days, and months) and large radial velocity (about +240 km s(-1)), the resulting Galactic restframe velocity is about 460 km s(-1), implying a bound retrograde orbit for this extreme halo object that currently crosses the Galactic plane at high speed.
Keywords: proper motions; stars: distances; stars: kinematics and dynamics; stars: Population II; subdwarfs; white dwarfs

AN EXTREMELY FAST HALO HOT SUBDWARF STAR IN A WIDE BINARY SYSTEM - Nemeth, Peter; Ziegerer, Eva; Irrgang, Andreas; Geier, Stephan; Fuerst, Felix; Kupfer, Thomas; Heber, Ulrich (Astrophysical Journal Letters, 2016)
New spectroscopic observations of the halo hyper-velocity star candidate SDSS J121150.27+143716.2 (V = 17.92 mag) revealed a cool companion to the hot subdwarf primary. The components have a very similar radial velocity and their absolute luminosities are consistent with the same distance, confirming the physical nature of the binary, which is the first double-lined hyper-velocity candidate. Our spectral decomposition of the Keck/ESI spectrum provided an sdB+K3V pair, analogous to many long-period subdwarf binaries observed in the Galactic disk. We found the subdwarf atmospheric parameters: T-eff = 30 600 +/- 500 K, log g= 5.57 +/- 0.06 cm s(-2), and He abundance log(nHe/nH)= -3.0 +/- 0.2. Oxygen is the most abundant metal in the hot subdwarf atmosphere, and Mg and Na lines are the most prominent spectral features of the cool companion, consistent with a metallicity of [Fe/H] = -1.3. The non-detection of radial velocity variations suggest the orbital period to be a few hundred days, in agreement with similar binaries observed in the disk. Using the SDSS-III flux calibrated spectrum we measured the distance to the system d = 5.5 +/- 0.5 kpc, which is consistent with ultraviolet, optical, and infrared photometric constraints derived from binary spectral energy distributions. Our kinematic study shows that the Galactic rest-frame velocity of the system is so high that an unbound orbit cannot be ruled out. On the other hand, a bound orbit requires a massive dark matter halo. We conclude that the binary either formed in the halo or was accreted from the tidal debris of a dwarf galaxy by the Milky Way.
Keywords: binaries: spectroscopic; Galaxy: halo; stars: atmospheres; stars: horizontal-branch; stars: kinematics and dynamics; subdwarfs

A progenitor binary and an ejected mass donor remnant of faint type Ia supernovae - Geier, S.; Marsh, T. R.; Wang, Bo; Dunlap, B.; Barlow, B. N.; Schaffenroth, Veronika; Chen, X.; Irrgang, Andreas; Maxted, P. F. L.; Ziegerer, Eva; Kupfer, Thomas; Miszalski, B.; et al. (Astronomy & Astrophysics, 2013)
Type Ia supernovae (SN Ia) are the most important standard candles for measuring the expansion history of the universe. The thermonuclear explosion of a white dwarf can explain their observed properties, but neither the progenitor systems nor any stellar remnants have been conclusively identified. Underluminous SN Ia have been proposed to originate from a so-called double-detonation of a white dwarf. After a critical amount of helium is deposited on the surface through accretion from a close companion, the helium is ignited causing a detonation wave that triggers the explosion of the white dwarf itself. We have discovered both shallow transits and eclipses in the tight binary system CD-30° 11223 composed of a carbon/oxygen white dwarf and a hot helium star, allowing us to determine its component masses and fundamental parameters. In the future the system will transfer mass from the helium star to the white dwarf. Modelling this process we find that the detonation in the accreted helium layer is sufficiently strong to trigger the explosion of the core. The helium star will then be ejected at such high velocity that it will escape the Galaxy. The predicted properties of this remnant are an excellent match to the so-called hypervelocity star US 708, a hot, helium-rich star moving at more than 750 km s-1, sufficient for it to leave the Galaxy. The identification of both progenitor and remnant provides a consistent picture of the formation and evolution of underluminous SNIa. © 2013 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs; Supernovae: general

Binaries discovered by the MUCHFUSS project: FBS 0117+396: An sdB+dM binary with a pulsating primary - Ostensen, R. H.; Geier, S.; Schaffenroth, Veronika; Telting, J. H.; Bloemen, S.; Nemeth, Peter; Beck, P. G.; Lombaert, R.; Papics, P. I.; Tillich, A.; Ziegerer, Eva; Fox Machado, L.; et al. (Astronomy & Astrophysics, 2013)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims to discover subdwarf-B stars with massive compact companions such as overmassive white dwarfs (M > 1.0 M âŠ™), neutron stars or black holes. From the 127 subdwarfs with substantial radial-velocity variations discovered in the initial survey, a number of interesting objects have been selected for extensive follow-up. After an initial photometry run with BUSCA revealed that FBS 0117+396 is photometrically variable both on long and short timescales, we chose it as an auxiliary target during a 6-night multi-color photometry run with Ultracam. Spectroscopy was obtained at a number of observatories in order to determine the binary period and obtain a radial-velocity amplitude. After establishing an orbital period of P = 0.252 d, and removing the signal associated with the irradiated hemisphere of the M-dwarf companion, we were able to detect ten pulsation periods in the Fourier spectrum of the light curve. Two pulsation modes are found to have short periods of 337 and 379 s, and at least eight modes are found with periods between 45 min and 2.5 h. This establishes that FBS 0117+396 is an sdB+dM reflection binary, in which the primary is a hybrid pulsator, and the first one found with this particular mélange of flavours. © ESO, 2013.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: close; Stars: individual: FBS 0117+396; Stars: oscillations; Subdwarfs; Surveys

Binaries discovered by the MUCHFUSS project: SDSS J162256.66 + 473051.1: An eclipsing subdwarf B binary with a brown dwarf companion - Schaffenroth, Veronika; Geier, Stephan; Heber, Ulrich; Kupfer, Thomas; Ziegerer, Eva; Heuser, Christian; Classen, Lew; Cordes, O. (Astronomy & Astrophysics, 2014)
Hot subdwarf B stars (sdBs) are core helium-burning stars located on the extreme horizontal branch. About half of the known sdB stars are found in close binaries. Their short orbital periods of 1.2 h to a few days suggest that they are post common-envelope systems. Eclipsing hot subdwarf binaries are rare but are important in determining the fundamental stellar parameters. Low-mass companions are identified by the reflection effect. In most cases, the companion is a main sequence star near the stellar mass limit. Here, we report the discovery of an eclipsing hot subdwarf binary SDSS J162256.66+473051.1 (J1622) with very short orbital period (0.0697 d), which has been found in the course of the MUCHFUSS project. The lightcurve shows grazing eclipses and a prominent reflection effect. An analysis of the light-and radial velocity (RV) curves indicated a mass ratio of q = 0.1325, an RV semi-amplitude K = 47.2 km s -1, and an inclination of i = 72.33°. We show that a companion mass of 0.064 MŠ(tm), which is well below the hydrogen-burning limit, is the most plausible solution, which implies a mass close to the canonical mass (0.47 MŠ(tm)) of the sdB star. Therefore, the companion is a brown dwarf, which has not only survived the engulfment by the red-giant envelope but also triggered its ejection and enabled the sdB star to form. The rotation of J1622 is expected to be tidally locked to the orbit. However, J1622 rotates too slowly (vrot = 74.5 ± 7 kmâ‰ s-1) to be synchronized, challenging tidal interaction models. © 2014 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: eclipsing; Binaries: spectroscopic; Brown dwarfs; Stars: fundamental parameters; Subdwarfs

Candidate hypervelocity stars of spectral type G and K revisited - Ziegerer, Eva; Volkert, Marco; Heber, Ulrich; Irrgang, Andreas; Gaensicke, B. T.; Geier, Stephan (Astronomy & Astrophysics, 2015)
Hypervelocity stars (HVS) move so fast that they are not bound to the Galaxy. When they were first discovered in 2005, dynamical ejection from the supermassive black hole (SMBH) in the Galactic centre (GC) was suggested as their origin. The two dozen HVSs known today are young massive B stars, mostly of 3-4 solar masses. Recently, 20 HVS candidates of low mass were discovered in the Segue G and K dwarf sample, but none of them originates from the GC. We embarked on a kinematic analysis of the Segue HVS candidate sample using the full 6D phase space information based on new proper motion measurements. Their orbital properties can then be derived by tracing back their trajectories in different mass models of our Galaxy. We present the results for 14 candidate HVSs for which proper motion measurements were possible. Significantly lower proper motions than found in the previous study were derived. Considering three different Galactic mass models, we found that all stars are bound to the Galaxy. We confirm that the stars do not originate from the GC. The distribution of their proper motions and radial velocities is consistent with predictions for runaway stars ejected from the Galactic disk by the binary supernova mechanism. However, their kinematics are also consistent with old disk membership. Moreover, most stars have rather low metallicities and strong alpha-element enrichment, as is typical for thick disk and halo stars, whereas the metallicity of the three most metal-rich stars might indicate that they are runaway stars from the thin disk. One start shows halo kinematics.
Keywords: stars: kinematics and dynamics; stars: low-mass; stars: late-type; stars: abundances; stars: Population II

Close Binary Progenitors and Ejected Companions of Thermonuclear Supernovae - Geier, S.; Kupfer, T.; Heber, Ulrich; Nemeth, Peter; Ziegerer, Eva; Irrgang, Andreas; Schindewolf, Markus; Marsh, T. R.; Gansicke, B. T.; Barlow, B. N.; Bloemen, S. (2017)
Hot subdwarf stars (sdO/Bs) are evolved core helium-burning stars with very thin hydrogen envelopes, which can be formed by common envelope ejection. Close sdB binaries with massive white dwarf (WD) companions are potential progenitors of thermonuclear supernovae type Ia (SN Ia). We discovered such a progenitor candidate as well as a candidate for a surviving companion star, which escapes from the Galaxy. More candidates for both types of objects have been found by cross-matching known sdB stars with proper motion and light curve catalogues. We found 72 sdO/B candidates with high Galactic restframe velocities, 12 of them might be unbound to our Galaxy. Furthermore, we discovered the second-most compact sdB+WD binary known. However, due to the low mass of the WD companion, it is unlikely to be a SN Ia progenitor.

Hot subdwarf stars and their connection to thermonuclear supernovae - Geier, S.; Kupfer, Thomas; Ziegerer, Eva; Heber, Ulrich; Nemeth, Peter; Irrgang, Andreas (Journal of Physics: Conference Series, 2016)
Hot subdwarf stars (sdO/Bs) are evolved core helium-burning stars with very thin hydrogen envelopes, which can be formed by common envelope ejection. Close sdB binaries with massive white dwarf (WD) companions are potential progenitors of thermonuclear supernovae type Ia (SN Ia). We discovered such a progenitor candidate as well as a candidate for a surviving companion star, which escapes from the Galaxy. More candidates for both types of objects have been found by crossmatching known sdB stars with proper motion and light curve catalogues. The Gaia mission will provide accurate astrometry and light curves of all the stars in our hot subdwarf sample and will allow us to compile a much larger all-sky catalogue of those stars. In this way we expect to find hundreds of progenitor binaries and ejected companions.
CRIS-Team Scopus Importer:2020-12-21

MUCHFUSS - Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS - Geier, Stephan; Schaffenroth, Veronika; Hirsch, H.; Tillich, A.; Heber, Ulrich; Maxted, P. F. L.; Ostensen, R. H.; Barlow, B. N.; O'Toole, S. J.; Kupfer, Thomas; Marsh, T.; Gaensicke, Boris T; et al. (Astronomische Nachrichten, 2012)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars with massive compact companions (white dwarfs with masses M > 1.0 M ⊙, neutron stars or black holes). The existence of such systems is predicted by binary evolution calculations and some candidate systems have been found. We identified ≃1100 hot subdwarf stars from the Sloan Digital Sky Survey (SDSS). Stars with high velocities have been reobserved and individual SDSS spectra have been analysed. About 70 radial velocity variable subdwarfs have been selected as good candidates for follow-up time resolved spectroscopy to derive orbital parameters and photometric follow-up to search for features like eclipses in the light curves. Up to now we found nine close binary sdBs with short orbital periods ranging from ≃0.07 d to 1.5 d. Two of them are eclipsing binaries with companions that are most likely of substellar nature © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs

Spectroscopic twin to the hypervelocity sdO star US 708 and three fast sdB stars from the Hyper-MUCHFUSS project - Ziegerer, Eva; Heber, Ulrich; Geier, Stephan; Irrgang, Andreas; Kupfer, Thomas; Fuerst, F.; Schaffenroth, Johannes (Astronomy & Astrophysics, 2017)
Important tracers for the dark matter halo of the Galaxy are hypervelocity stars (HVSs), which are faster than the local escape velocity of the Galaxy and their slower counterparts, the high-velocity stars in the Galactic halo. Such HVSs are believed to be ejected from the Galactic centre (GC) through tidal disruption of a binary by the super-massive black hole (Hills mechanism). The Hyper-MUCHFUSS survey aims at finding high-velocity potentially unbound hot subdwarf stars. We present the spectroscopic and kinematical analyses of a He-sdO as well as three candidates among the sdB stars using optical Keck/ESI and VLT (X-shooter, FORS) spectroscopy. Proper motions are determined by combining positions from early-epoch photographic plates with those derived from modern digital sky surveys. The Galactic rest frame velocities range from 203 km s(-1) to 660 km s(-1), indicating that most likely all four stars are gravitationally bound to the Galaxy. With T-eff = 47 000 K and a surface gravity of log g = 5 : 7, SDSS J205030.39-061957.8 (J2050) is a spectroscopic twin of the hypervelocity He-sdO US 708. As for the latter, the GC is excluded as a place of origin based on the kinematic analysis. Hence, the Hills mechanism can be excluded for J2050. The ejection velocity is much more moderate (385 +/- 79 km s(-1)) than that of US 708 (998 +/- 68 km s(-1)). The binary thermonuclear supernova scenario suggested for US 708 would explain the observed properties of J2050 very well without pushing the model parameters to their extreme limits, as required for US 708. Accordingly, the star would be the surviving donor of a type Ia supernova. Three sdB stars also showed extreme kinematics; one could be a HVS ejected from the GC, whereas the other two could be ejected from the Galactic disk through the binary supernova mechanism. Alternatively, they might be extreme halo stars.
Keywords: stars: kinematics and dynamics; subdwarfs; stars: atmospheres; Galaxy: halo

The catalogue of radial velocity variable hot subluminous stars from the MUCHFUSS project - Geier, S.; Kupfer, Thomas; Heber, Ulrich; Schaffenroth, Veronika; Barlow, B. N.; Ostensen, R. H.; O'Toole, S. J.; Ziegerer, Eva; Heuser, Christian; Maxted, P. F. L.; Gaensicke, B. T.; Marsh, T. R.; et al. (Astronomy & Astrophysics, 2015)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims to find sdBs with compact companions such as massive white dwarfs, neutron stars, or black holes. Here we provide classifications, atmospheric parameters, and a complete radial velocity (RV) catalogue containing 1914 single measurements for a sample of 177 hot subluminous stars discovered based on SDSS DR7; 110 stars show significant RV variability, while 67 qualify as candidates. We constrain the fraction of close massive compact companions of hydrogen-rich hot subdwarfs in our sample to be smaller than ∼1.3%, which is already close to the theoretical predictions. However, the sample might still contain such binaries with longer periods exceeding ∼8 d. We detect a mismatch between the ΔRVmax-distribution of the sdB and the more evolved sdOB and sdO stars, which challenges our understanding of their evolutionary connection. Furthermore, irregular RV variations of unknown origin with amplitudes of up to ∼180 km s-1 on timescales of years, days, and even hours have been detected in some He-sdO stars. They might be connected to irregular photometric variations in some cases.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Stars: atmospheres; Stars: horizontal-branch; Subdwarfs

The catalogue of radial velocity variable hot subluminous stars from the MUCHFUSS project (vol 577, pg A26, 2015) - Geier, S.; Kupfer, T.; Heber, Ulrich; Schaffenroth, Veronika; Barlow, B. N.; Ostensen, R. H.; O'Toole, S. J.; Ziegerer, Eva; Heuser, Christian; Maxted, P. F. L.; Gansicke, B. T.; Marsh, T. R.; et al. (Astronomy & Astrophysics, 2017)
Keywords: binaries: spectroscopic; subdwarfs; stars: horizontal branch; stars: atmospheres; errata; addenda

The EREBOS project: Investigating the effect of substellar and low-mass stellar companions on late stellar evolution Survey, target selection, and atmospheric parameters - Schaffenroth, V.; Barlow, B. N.; Geier, S.; Vuckovic, M.; Kilkenny, D.; Wolz, Maximilian; Kupfer, T.; Heber, Ulrich; Drechsel, Horst; Kimeswenger, S.; Marsh, T.; Wolf, M.; et al. (Astronomy & Astrophysics, 2019)
Eclipsing post-common-envelope binaries are highly important for resolving the poorly understood, very short-lived common-envelope phase of stellar evolution. Most hot subdwarfs (sdO/Bs) are the bare helium-burning cores of red giants that have lost almost all of their hydrogen envelope. This mass loss is often triggered by common-envelope interactions with close stellar or even substellar companions. Cool companions to hot subdwarf stars such as late-type stars and brown dwarfs are detectable from characteristic light-curve variations - reflection effects and often eclipses. In the recently published catalog of eclipsing binaries in the Galactic Bulge and in the Asteroid Terrestrial-impact Last Alert System (ATLAS) survey, we discovered 125 new eclipsing systems showing a reflection effect seen by visual inspection of the light curves and using a machine-learning algorithm, in addition to the 36 systems previously discovered by the Optical Gravitational Lesing Experiment (OGLE) team. The Eclipsing Reflection Effect Binaries from Optical Surveys (EREBOS) project aims at analyzing all newly discovered eclipsing binaries of the HW Vir type (hot subdwarf + close, cool companion) based on a spectroscopic and photometric follow up to derive the mass distribution of the companions, constrain the fraction of substellar companions, and determine the minimum mass needed to strip off the red-giant envelope. To constrain the nature of the primary we derived the absolute magnitude and the reduced proper motion of all our targets with the help of the parallaxes and proper motions measured by the Gaia mission and compared those to the Gaia white-dwarf candidate catalog. It was possible to derive the nature of a subset of our targets, for which observed spectra are available, by measuring the atmospheric parameter of the primary, confirming that less than 10% of our systems are not sdO/Bs with cool companions but are white dwarfs or central stars of planetary nebula. This large sample of eclipsing hot subdwarfs with cool companions allowed us to derive a significant period distribution for hot subdwarfs with cool companions for the first time showing that the period distribution is much broader than previously thought and is ideally suited to finding the lowest-mass companions to hot subdwarf stars. The comparison with related binary populations shows that the period distribution of HW Vir systems is very similar to WD+dM systems and central stars of planetary nebula with cool companions. In the future, several new photometric surveys will be carried out, which will further increase the sample of this project, providing the potential to test many aspects of common-envelope theory and binary evolution.
CRIS-Team WoS Importer:2019-10-11

The fastest unbound star in our Galaxy ejected by a thermonuclear supernova - Geier, Stephan; Furst, Felix; Ziegerer, Eva; Kupfer, Thomas; Heber, Ulrich; Irrgang, Andreas; Wang, Bo; Liu, Z.; Han, Z.; Sesar, B.; Levitan, D.; Kotak, R.; et al. (Science, 2015)
Hypervelocity stars (HVSs) travel with velocities so high that they exceed the escape velocity of the Galaxy. Several acceleration mechanisms have been discussed. Only one HVS (US 708, HVS 2) is a compact helium star. Here we present a spectroscopic and kinematic analysis of US 708. Traveling with a velocity of similar to 1200 kilometers per second, it is the fastest unbound star in our Galaxy. In reconstructing its trajectory, the Galactic center becomes very unlikely as an origin, which is hardly consistent with the most favored ejection mechanism for the other HVSs. Furthermore, we detected that US 708 is a fast rotator. According to our binary evolution model, it was spun-up by tidal interaction in a close binary and is likely to be the ejected donor remnant of a thermonuclear supernova.

The MUCHFUSS photometric campaign - Schaffenroth, Veronika; Geier, S.; Heber, Ulrich; Gerber, Raoul; Schneider, David; Ziegerer, Eva; Cordes, O. (Astronomy & Astrophysics, 2018)
Hot subdwarfs (sdO/Bs) are the helium-burning cores of red giants, which have lost almost all of their hydrogen envelope. This mass loss is often triggered by common envelope interactions with close stellar or even substellar companions. Cool companions like late-type stars or brown dwarfs are detectable via characteristic light-curve variations like reflection effects and often also eclipses. To search for such objects, we obtained multi-band light curves of 26 close sdO/B binary candidates from the MUCHFUSS project with the BUSCA instrument. We discovered a new eclipsing reflection effect system (P = 0 : 168938 d) with a low-mass M dwarf companion (0.116 M-circle dot). Three more reflection effect binaries found in the course of the campaign have already been published; two of them are eclipsing systems, and in one system only showing the reflection effect but no eclipses, the sdB primary is found to be pulsating. Amongst the targets without reflection effect a new long-period sdB pulsator was discovered and irregular light variations were found in two sdO stars. The found light variations allowed us to constrain the fraction of reflection effect binaries and the substellar companion fraction around sdB stars. The minimum fraction of reflection effect systems amongst the close sdB binaries might be greater than 15% and the fraction of close substellar companions in sdB binaries may be as high as 8 .0%. This would result in a close substellar companion fraction to sdB stars of about 3%. This fraction is much higher than the fraction of brown dwarfs around possible progenitor systems, which are solar-type stars with substellar companions around 1AU, as well as close binary white dwarfs with brown dwarf companions. This might suggest that common envelope interactions with substellar objects are preferentially followed by a hot subdwarf phase.
Keywords: subdwarfs; binaries: eclipsing; binaries: spectroscopic; brown dwarfs; stars: fundamental parameters